Examining reporting and representation of patients with cancer in COVID‐19 clinical trials. Issue 4 (23rd February 2021) - Rabow, Maya; Wang, Christine; Zhang, Sylvia; Tahir, Peggy Mary; Small, Eric J.; Borno, Hala T.
Abstract: Background: Patients with cancer are particularly vulnerable in the current COVID‐19 pandemic. Emerging evidence suggests that patients with a cancer diagnosis are three times more likely to die from COVID‐19 compared to non‐cancer patients. Due to these observed risks, it is critical that emerging COVID‐19 therapies demonstrate safety and efficacy among patients with cancer. Aim: This study sought to examine reporting and representation of patients with cancer among published COVID‐19 treatment‐related research studies. Methods and results: All published COVID‐19 treatment‐related clinical research studies published from March 1 to August 20, 2020 recruiting from North America and Europe were identified. The date published, study design, therapeutics studied, and study population were evaluated. Of the 343 studies identified through initial search and researcher knowledge, 55 (16%) reported on COVID‐19 treatments. Twenty‐one COVID‐19 therapeutic studies (n = 15, prospective; n = 6, retrospective) that recruited from the United States and Europe were identified. Among these studies, eight (38%) reported on the number of trial participants with a cancer diagnosis in the publication and two (10%) specified tumor type. Four of the studies (19%) did not collect cancer history. Among studies where cancer history was available, patients with a cancer diagnosis participated at a proportion higher than overall cancer prevalence and greater than the known proportion of COVID‐19 patients with cancer. Conclusion: This study observed that cancer history was not uniformly collected or reported among published COVID‐19 therapeutic studies. Among reported publications, we observed that patients with a cancer diagnosis were generally overrepresented. However, patients with a cancer diagnosis were notably underrepresented in outpatient COVID‐19 therapeutic studies.